Increased Complexities in Visual Search Behavior in Skilled Players for a Self-Paced Aiming Task - Chia, Jingyi S.; Burns, Stephen F.; Barrett, Laura A.; Chow, Jia Y. (Frontiers in Psychology, 2017)
The badminton serve is an important shot for winning a rally in a match. It combines good technique with the ability to accurately integrate visual information from the shuttle, racket, opponent and intended landing point. Despite its importance and repercussive nature, to date no study has looked at the visual search behaviors during badminton service in the singles discipline. Unlike anticipatory tasks (e.g. shot returns), the serve presents an opportunity to explore the role of visual search behaviors in movement control for self-paced tasks. Accordingly, this study examined skill-related differences in visual behavior during the badminton singles serve. Skilled (n = 12) and less skilled (n = 12) participants performed 30 serves to a live opponent, while real-time eye movements were captured using a mobile gaze registration system. Frame-by-frame analyses of 665 serves were made and the skilled players took a longer preparatory time before serving. Visual behavior of the skilled players was characterized by significantly greater number of fixations on more areas of interest per trial than the less skilled. In addition, the skilled players spent a significantly longer time fixating on the court and net, whereas the less skilled players found the shuttle to be more informative. Quiet eye (QE) duration (indicative of superior sports performance) however, did not differ significantly between groups which has implications on the perceived importance of QE in the badminton serve. Moreover, while visual behavior differed by skill level, considerable individual differences were also observed especially within the skilled players. This augments the need for not just group-level analyses, but individualised analysis for a more accurate representation of visual behavior. Findings from this study thus provide an insight to the possible visual search strategies as players serve in net-barrier games. Moreover, this study highlighted an important aspect of badminton relating to deception and the implications of interpreting visual behavior of players.